1970
DOI: 10.1007/bf01868012
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the polar moiety of lipids on bilayer conductance induced by uncouplers of oxidative phosphorylation

Abstract: Bilayer membranes were formed from decane, cholesterol, and three lipids isolated fromStaphylococcus aureus: positively charged lysyl phosphatidylglycerol (LysPG), negatively charged phosphatidylglycerol (PG), and neutral diglucosyldiglyceride (DiGluDiGly). The uncouplers of oxidative phosphorylation, 2,4-dinitrophenol (DNP) and 3-t-butyl,5-chloro,2'-chloro,4'-nitrosalicylanilide (S 13), increased the electrical conductance of all three differently charged bilayers. S 13 was found to be the most effective reag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

1972
1972
1991
1991

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 16 publications
3
22
0
Order By: Relevance
“…where o-is the charge density in electronic charges per A 2, C is the total monovalent ion concentration in the bulk solution in moles per liter and RT]F= 25.3 mV at 22 ~ The data of Hopfer et al (1970) illustrate, however, that the ratio of the conductances produced by DNP on a neutral and positive bilayer membrane is much less than that predicte& by the combination of Eqs. (8) and (9) and, furthermore, that the ratio depends markedly on the pH.…”
Section: The Carrier Modelmentioning
confidence: 63%
See 3 more Smart Citations
“…where o-is the charge density in electronic charges per A 2, C is the total monovalent ion concentration in the bulk solution in moles per liter and RT]F= 25.3 mV at 22 ~ The data of Hopfer et al (1970) illustrate, however, that the ratio of the conductances produced by DNP on a neutral and positive bilayer membrane is much less than that predicte& by the combination of Eqs. (8) and (9) and, furthermore, that the ratio depends markedly on the pH.…”
Section: The Carrier Modelmentioning
confidence: 63%
“…(7) that irrespective of the value of ~ the conductance should attain a maximum value when [H § =K1. Hopfer et al (1970) observed, however, that the conductance maximum was shifted about a pH unit to the acid side of the pK when measurements were made with 10-4M DNP on a bilayer formed from a positive lipid. Next, Eq.…”
Section: The Carrier Modelmentioning
confidence: 83%
See 2 more Smart Citations
“…The mechanism of action of these agents is most simply explained in terms of their well-documented ability to increase proton conductance across model membrane systems (5,6) and t o inhibit energy-linked proton movement in energytransducing membranes (e.g., Ref. 7).…”
Section: Introductionmentioning
confidence: 99%